Controlling the Growth of Extremely Halophilic Bacteria on Brine Cured Cattle Hides - (:unkn) unknown (Society of Leather Technologists and Chemists, 2000)
Six commercially available brine raceway bactericides were tested for their ability to prevent the growth of extremely halophilic bacteria isolated from hides that were brine cured in either the US or Canada. These products were used at their recommended raceway doses and at two times and four times that amount. The active ingredients of the commercially available bactericides were: naphthalene and 1-2 dichlorobenzene (Bactericide A), trichloro-S-triazinetrione and sodium sulphate (Bactericide B), sodium bisulfite and acetic acid (Bactericide C), alkyl phenol ethoxylate and potassium dimethyl dithrocarbonate (Bactericide D), 2(thiocyanomethylthio) benzothiazole and methylene bis (thiocyanate) (Bactericide E), sodium-ortho-phenylphenate and ortho-benzyl-para-chlorophenol (Bactericide F). Bactericides A, B and E were found to be effective in preventing growth of the extremely halophilic bacteria tested. Bactericides C, D and F were found to be ineffective at the concentrations tested. All of the extremely halophilic isolates used in this experiments showed positive gelatinase activity.